Multiple Input–Single Output (MISO) Framework for Low Velocity Impact Response of Hybrid Gongronema latifolium/S-Glass Fibre Epoxy Composites - Okafor, Christian Emeka; Ugwu, Peter Chukwuemeka; Ekwueme, Godspower Onyekachukwu; Akçakale, Nürettin; Nwanna, Emmanuel Chukwudi (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Sustainable composites are vital for impact-critical aerospace, automotive, and defense applications. This study used Multiple Input–Single Output (MISO) experimental approach to assess how hybrid ratio, mass fraction, and fiber orientation influence the low-velocity impact behavior of Gongronema/S-glass epoxy composites. Gongronema fibers and S-glass were combined with ER-F292 epoxy and molded into ASTM-standard samples. Charpy impact tests measured energy absorption. A 60-run design evaluated input variable combinations, and Multiple Linear Regression identified significant predictors using p-values and confidence intervals. Results showed that the mean values for hybridization ratio, mass fraction, fiber orientation, and low velocity impact were (2.50), (27.79%), (67.90°), and (3.82 J), respectively. It was found that the mass fraction had significant negative correlation with low velocity impact (r = -0.455; p = 0.000), as did the fiber orientation (r = -0.853; p = 0.000). The results for R = (0.994), R² = (0.989), F = (1607.390), and Durbin-Watson = (2.213) show that the regression model is highly predictive. Regression coefficients indicated negative effects from hybridization ratio (-0.357), mass fraction (-0.032), and fiber orientation (-0.017), all statistically significant (p = 0.000). Residual plots confirmed model validity. The TEM images of confirmation test sample 1 reveal fiber-matrix interfaces with particle sizes between 10.02–26.40 nm. Variations in scale (100 nm and 50 nm) show microstructural differences, suggesting strong adhesion, dispersion aggregation, and anisotropic behavior due to 90-degree fiber orientation within epoxy matrix. The study concludes that strategic optimization of input parameters significantly enhances the impact resistance of hybrid biocomposites.